Is screen time really harmful to children? - Ng, Alvin Lai Oon * (Star Media Group Berhad, 2023)
“Doctor, is it safe to give my eight-year-old son a handphone? Isn’t screen time good for children?” It’s easy to answer that with a resounding no, but that’s oversimplifying the issue, and the topic of screen time among children and teenagers is complex and multifactorial.